Measuring changes in counseling ethics education: a preliminary study - Zakaria, Noor Syamilah; Bakar, Ab. Rahim; Zakaria, Ezalinda; Subarimaniam, Neerushah; Warren, Jane; Weatherford, Jennifer; Kocet, Michael (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
Counselors are expected to have significant knowledge regarding ethical considerations for providing effective counseling services to clients. This pedagogical innovation session will disseminate findings from a preliminary study to measure counseling ethical competencies among counseling students, who participated in an experiential-based counseling ethics education course. Research in education confirms that experiential-based activities can be an excellent teaching strategy; given it promotes the natural interest within students, creates a meaningful and fun learning environment, enhances long-term memory and productivity, and produces a defined set of skills to survive in later life. The Counseling Ethics Audit (CEA) instrument was used to assess three important areas of counseling students’ ethical competencies that include ethical sensitivity, ethical skills, and ethical training. The audience will learn about the CEA as a new instrument to measure ethical knowledge learning outcomes among counseling students; identify the significant positive changes across three measures of ethical competence; and learn different experiential activities that can be utilized in counseling ethics education course instruction. The information from this session will nurture counseling ethics competencies comprehension and application that support counseling students learning within and beyond the curriculum and its core; toward becoming better counseling professionals and establishing a brighter counseling profession.